Screening of the Relaxivity of Gadolinium‐Loaded Periodic Mesoporous Silica Functionalized by Means of Soft Metalorganic Silylamide Grafting. Issue 35 (6th November 2013) - Skår, Hjørdis; Seland, John G.; Liang, Yucang; Frøystein, Nils Å.; Törnroos, Karl W.; Anwander, Reiner
Abstract: Soft metalorganic grafting of periodic mesoporous silica (PMS) materials is introduced as a method for obtaining nanostructured Gd III ‐loaded silica particles with relatively high 1 H relaxivity. The silylamide complex Gd[N(SiHMe2 )2 ]3 (THF)2 was grafted onto MCM‐41, SBA‐15, and SBA‐1, thereby providing PMSs of distinct symmetry as well as pore size and configuration. The materials were characterized by infrared spectroscopy, elemental analysis, powder X‐ray diffraction (PXRD), N2 physisorption, and scanning as well as transmission electron microscopy (SEM/TEM). Relaxivities up to 15.8 mM –1  s –1 were determined at high magnetic field strength (400 MHz). The nuclear magnetic resonance dispersion (NMRD) data of a calcined Gd[N(SiHMe2 )2 ]3 (THF)2 @SBA‐1 material had a shape typical for slow‐tumbling systems, with a maximum at approximately 50 MHz. Temperature‐dependence studies of the relaxivity ( r 1 ) indicated that the grafted materials were characterized by an efficient water exchange. To maintain a high relaxivity, a low (1 wt.‐%) Gd III loading and a hydrophilic surface had to be provided. Varying the topology of the silica support only resulted in small variations in r 1 of the hybrid materials. Abstract : Grafting Gd[N(SiHMe2 )2 ]3 (THF)2 onto mesoporous silica gives hybrid materials with interesting 1 H relaxometric properties at high field strength. A low Gd III loading and a hydrophilic silica surface are necessary to maintain a high relaxivity.